Sylvian aqueduct syndrome as a sign of acute obstructive hydrocephalus in children. - Chattha, A S (1975)
Eight cases of obstructive hydrocephalus manifesting palsy of upward gaze and other features of the Sylvian aqueduct syndrome are reported. During the crisis of intracranial hypertension, all of them developed upward gaze palsy and variable abnormalities of the convergence mechanism such as paralysis, spasm, and convergence nystagmus. The frequent apparent blindness was probably related to gaze paralysis, since visual evoked responses were present. All these ocular abnormalities disappeared after shunting. Periaqueductal dysfunction on the basis of raised intracranial pressure is postulated as the possible mechanism for the above ocular manifestations. The 'setting sun' sign is frequently seen in infants and children with hydrocephalus and has been considered in the past to result from displacement of eyeballs by pressure from the orbital roof plate. Our observations would suggest periaqueductal dysfunction rather than the mechanical displacement as the possible mechanism for this sign.